A parametric study on the stability of fiber reinforced rubber bearings under combined axial and shear loads. (15th January 2021) - Calabrese, Andrea; Spizzuoco, Mariacristina; Galano, Simone; Tran, Nghiem; Strano, Salvatore; Terzo, Mario
Highlights: Aims to shedding some light on the behavior of unbonded FRBs. The influence of axial load, material properties, primary and secondary shape factors, are discussed. Numerical models of FRBs have been analyzed using advanced tools for FEAs. All forms of nonlinearities are considered, including material, geometric and contact ones. Abstract: Fiber Reinforced Bearings (FRBs) have proven to be a valuable rubber-based base isolation technology in which flexible fiber reinforcements are used to replace the steel layers commonly adopted for the manufacturing of Laminated Rubber Bearings (LRBs). Thanks to the low weight and cost of FRBs, these devices could prove to be instrumental for the promotion of base isolation applications to houses and residential buildings of developing countries of the world in seismic regions. This study is based on the results of a large set of Finite Element Analyses (FEAs) aimed to assessing the performance of FRBs under combined axial and shear loads. The aim of this work is that of filling a lack of knowledge regarding the lateral displacement capacity of FRBs: research studies available in literature do not consider the effects of axial pressure, material properties, primary and secondary shape factors on the response of these devices under combined axial and lateral loads. Conclusions of this study underline that the simple design formula commonly adopted for the design of FRBs underestimate the effect of the axial pressure in limiting the lateral displacement capacity of the bearings. Moreover, available simplified formula, do not offer an accurate estimate of the force response of these bearings under combined loads. Additional FEAs are needed to extend the results of this study to bearings of other shapes, including circular and square isolators.